Study of parcels-based Land Use Planning in Urban areas dan Rural Areas (Case Study of Mantrijeron Sub-district, Yogyakarta City and Bambanglipuro Sub-district, Bantul Regency) - Hary Listantyo Prabowo (Jurnal Geospasial Indonesia, 2019)
The Land Use Planning (LUP-Neraca Penatagunaan Tanah/NPGT) is a balance between land availability and the needs of tenure, use and utilization of land according to the Regional Spatial Plan (RTRW) function area. LUP is arranged sectorally and regionally. Examples of sectoral LUP are rice field planning and plantation field planning. While regional LUP is arranged at a certain administrative level. So far LUP has been prepared based on zones/ regions that are adjusted to the RTRW functions area. The LUP at the sub-district administrative level began to be initiated and to be implemented after almost all of district/ city LUPs were implemented. Sub-district LUP was supported by the availability of the Subdistrict Spatial Detail Plan (RDTR) on a 1:5.000 scale which became a reference in the permittance of space utilization, so that the subdistrict LUP was arranged on the same scale. In this paper an assessment of sub-district LUP was made based on the Parcels Map (PBT) that available in the land office. PBT displays land parcels based on land ownership and land tenure. LUP is carried out in urban areas and rural areas. Location of urban areas in Mantrijeron Sub-District, Yogyakarta City, while rural areas in Bambanglipuro Sub-District.The stages of sub-district LUP consist of : data collection/ inventory; processing and analysis of data; and compilation of results and discussion. The data collection/ inventory phase includes activities for preparing work maps and collecting primary data and supporting data. The processing and analysis stage includes data processing on sub-district LUP compilation with GIS application (ArcGIS) and LUP analysis. LUP analysis consists of : analysis of land use changes, analysis of land use suitability and analysis of land availability. The stage of result preparation and discussion includes the preparation of the result of the analysis, a comparison between two regions that were studied, conclusions and recommendations. The result of the parcels-based sub-district LUP shows that land tenure and ownership information is very detailed; the information of land use and utilization in one parcel of land can consist of more than one type. In urban areas, the size of land parcels is relatively small with more varied types of land use and utilization than rural areas. As a note, that the coverage of parcels map in rural areas still needs to be improved because there are still empty areas.